Peran live Streaming dan Diskon Dalam Meningkatkan Loyalitas Pelanggan Pada Tiktok Shop - Viktoria Tridelfi Luruk; Myra Andriana; Robby Andika Kusumajaya (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study aims to analyze the influence of Live Streaming and Discounts on Customer Loyalty on the TikTok Shop platform in Semarang Regency. The type of research chosen is quantitative with a causal approach, selecting a sample of 100 Generation Z respondents who were decided using a purposive sampling technique. Data were obtained from an online questionnaire and analyzed in SPSS with a multiple linear regression method. The study findings indicate that Live Streaming has a positive and significant effect on Customer Loyalty (t count = 3.384; p = 0.001), as well as Discounts have a positive and significant effect (t count = 5.765; p < 0.001). Simultaneous analysis shows that both independent variables simultaneously have a significant effect on Customer Loyalty (F count = 30.229; p < 0.001), with an Adjusted R² score of 0.371. These findings indicate that marketing strategies based on Live Streaming and Discounts can increase consumer engagement and loyalty on TikTok Shop.